PENGARUH LATIHAN PLYOMETRIK MELOMPAT MELEWATI RINTANGAN DENGAN DUA KAKI & SATU KAKI KE DEPAN DAN LATIHAN PLYOMETRIK MELOMPAT MELEWATI RINTANGAN DENGAN DUA KAKI & SATU KAKI KE SAMPING TERHADAP KEMAMPUAN POWER OTOT TUNGKAI - Amrizal Amrizal (STKIP ROKANIA, 2019)
In swimming pool athletes Belibis Pekanbaru has not shown maximum results, this is due to muscle limb muscle athletes who have not been good. The type of research is quasi experiment the sampling technique using proportional random sampling technique.the population in this athlets swimming belibis pekanbaru amounted to 22 people. in this case sample on KU.III age 12-13 years athlets swimming pool club belibis pekanbaru with the number of 20 people. Based on the above description it is concluded that the hypothesis that 1) The form of standing jump over two leg & single leg to forward exercise significantly influence the ability of limb muscle of Belibis Pekanbaru at 6.79, 2) Form of standing jump over two leg & single leg to side have significant effect to increase of limb muscle power capacity of athlete Belibis Pekanbaru equal to 5.07, 3) There is differnce of influence of form of exercise of standing jump over two leg & single leg to forward and to side increase the ability of muscle leg muscle athlets Belibis Pekanbaru by 2.03.